Localization of metastasis within the sentinel lymph node biopsies: a predictor of additional axillary spread of breast cancer? - César Augusto Alvarenga; César Cabello dos Santos; Marcelo Alvarenga; Paula Itagyba Paravidino; Sirlei Siani Morais; Henrique Benedito Brenelli; Filomena Marino de Carvalho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2013)
PURPOSE: To explore the relationship between morphological characteristics and histologic localization of metastasis within sentinel lymph nodes (SLN) and axillary spread in women with breast cancer. METHODS: We selected 119 patients with positive SLN submitted to complete axillary lymph node dissection from July 2002 to March 2007. We retrieved the age of patients and the primary tumor size. In the primary tumor, we evaluated histologic and nuclear grade, and peritumoral vascular invasion (PVI). In SLNs we evaluated the size of metastasis, their localization in the lymph node, number of foci, number of involved lymph nodes, and extranodal extension. RESULTS: Fifty-one (42.8%) patients had confirmed additional metastasis in non-sentinel lymph nodes (NLSN). High histologic grade, PVI, intraparenchymatous metastasis, extranodal neoplastic extension and size of metastasis were associated with positive NLSN. SLN metastasis affecting the capsule were associated to low risk incidence of additional metastasis. After multivariate analysis, PVI and metastasis size in the SLN remained as the most important risk factors for additional metastasis. CONCLUSIONS:The risk of additional involvement of NSLN is higher in patients with PVI and it increases progressively according the histologic localization in the lymph node, from capsule, where the afferent lymphatic channel arrives, to the opposite side of capsule promoting the extranodal extension. Size of metastasis greater than 6.0 mm presents higher risk of additional lymph node metastasis.